The role of school principals’ growth mindset-based leadership as a foundation for deep learning in gunung mas regency - WULANDARI, AGTRI; Meiliawati, Ruli; Sidauruk, Suandi (IAIN Palangka Raya, 2025)
This study aims to examine the role of school principals in Gunung Mas Regency in cultivating a growth mindset as the foundation for deep learning. The research employed a descriptive method through document analysis using the Mindset Mapping Instrument developed by the Directorate General of Teachers and Education Personnel (GTK Dikdasmen) in 2025. The findings show that most principals fall within the Fixed–Growth category (48,2%), followed by Growth–Fixed (21,4%), Growth–Growth (17,9%), and Fixed–Fixed (12,5%). Principals with a growth mindset tend to be open to criticism, view mistakes as part of the learning process, and value effort, although some remain constrained by fear of failure and performance orientation. The implications of this study highlight that strengthening growth mindset leadership is crucial for enabling principals to serve as role models and key drivers in implementing adaptive, innovative, and sustainable deep learning practices.